Treatment initiation rates of patients with positive anti-hepatitis C virus results in tertiary hospitals in Turkey - Mustafa K Çelen; Buket Ertürk Şengel; Şafak Kaya; Neşe Demirtürk; Alpay Azap; Hüsnü Pullukçu; Esma Eroğlu; Figen Yıldırım; Hüseyin Ş Barut; Esra Zerdali; Ayşe Sağmak Tartar; Ayşe Ö Mete; et al. (Journal of Infection in Developing Countries)
Introduction: The aim of this national, multicenter, cross-sectional, retrospective chart review study was to determine the proportion of patients in Turkey who received hepatitis C virus (HCV) treatment after receiving positive anti-HCV results during HCV screening.